India : Sustaining Reform, Reducing Poverty - World Bank (New Delhi: Oxford University Press, 2013)
The report analyzes India ' s continued good progress in increasing incomes, and improving living standards over the past decade, which after the setback associated with the 1991 balance of payments crisis, economic growth picked up, income poverty continued to decline, and many social indicators, in particular literacy, continued to improve. Likewise, there has been an opening to private activity, trade policy and the exchange rate regime have been further liberalized, and capital markets have been reformed, leading to an improved investment climate. Nonetheless, development progress has been steady, but uneven, while in addition, the recent growth deceleration was accompanied by a slowdown in investment, especially in the private sector. The fiscal position of the general government has now also deteriorated, with a rising budget deficit, the result of a significant increase in government consumption, and continued low revenue mobilization. But at the same time, prudent monetary policy has helped contain inflation, and strengthen the balance of payments. Based on this analysis, fiscal reforms are needed in taxation, financial, social, as well as for fiscal management. The report also reviews the delivery of public services, showing the need to access effective social safety nets, i.e., social services that require increasing the level, but more importantly the quality of public expenditures in these areas. This in turn requires improving the governance and productivity of India ' s civil service, and the pressing problem of affordability. An effective program of civil service reform should include measures to achieve the following three objectives: improve access to information; strengthen accountability; and, reduce political interference. Of special concern, are the weaknesses in the service delivery of social sectors: education, health and social safety nets, and, it has been argued that decentralization, and local empowerment will ultimately improve the quality of service delivery at the village level. The report suggests improving the investment climate, with a special look at infrastructure development, while promoting rapid agricultural, and rural growth given its importance in the socioeconomic, and political fabric of India, through productivity-enhancing investments.